Limits to commercially iodized salt to address dietary iodine deficiency in rural Papua New Guinea - Benson, Todd; Schmidt, Emily; Namusoke, Hanifa; Temple, Victor J.; Holtemeyer, Brian; Codling, Karen; Rudert, Christiane (HEC Press, 2020)
Background and Objectives: Fortifying commercial table salt with iodine is the principal strategy used globally to prevent dietary iodine deficiency. However, the costs of providing fortified salt to remote communities may result in it not being locally available or too expensive for many households. This study shows that barriers to consuming adequately iodized salt remain significant for remote rural households in Papua New Guinea (PNG). Methods and Study Design: Using data from a rural household survey conducted in four areas of PNG in 2018, two issues are examined. First, we contrast the characteristics of households that reported consuming or not consuming iodized table salt, respectively. Second, the adequacy of the iodine content of samples of table salt consumed was assessed in the laboratory. Results: Nine percent of the 1,026 survey households reported not consuming iodized table salt. These households tend to live in remote communities, are among the poorest households, have received no formal education, and have experienced recent food insecurity. Second, 17 percent of the 778 salt samples tested had inadequate iodine. The brand of salt most commonly consumed had the highest share of samples with inadequate iodine levels. Conclusions: Particularly in remote communities, ensuring that individuals consume sufficient iodine will require going beyond salt iodization to use other approaches to iodine supplementation. To ensure that the iodine intake of those using commercial table salt is adequate, closer monitoring of the iodine content in table salt produced or imported into PNG and enforcement of salt iodization regulations is required.